2011
DOI: 10.1007/s11721-010-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Swarm cognition on off-road autonomous robots

Abstract: This paper contributes with the first validation of swarm cognition as a useful framework for the design of autonomous robots controllers. The proposed model is built upon the authors' previous work validated on a simulated robot performing local navigation on a 2-D deterministic world. Based on the ant foraging metaphor and motivated by the multiple covert attention hypothesis, the model consists of a set of simple virtual agents inhabiting the robot's visual input, searching in a collectively coordinated way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…To close the gap between swarm cognition and individual cognitive behaviour, Santana and Correia Santana and Correia (2010) and (Santana and Correia, 2011) studied how the stigmergic behaviour displayed by foraging army ants could be employed to implement robot behaviour in natural environments. The study encompassed the development of a control system composed of a set of simple virtual agents inhabiting the robot's visual input, called p-ants.…”
Section: Artificial Swarm Cognitionmentioning
confidence: 99%
“…To close the gap between swarm cognition and individual cognitive behaviour, Santana and Correia Santana and Correia (2010) and (Santana and Correia, 2011) studied how the stigmergic behaviour displayed by foraging army ants could be employed to implement robot behaviour in natural environments. The study encompassed the development of a control system composed of a set of simple virtual agents inhabiting the robot's visual input, called p-ants.…”
Section: Artificial Swarm Cognitionmentioning
confidence: 99%
“…Typically, the volumetric signature of obstacles is used for their detection from range data acquired by either laser scanners [8,42,39,24] or binocular vision systems [22,30,34,32]. Monocular appearance cues are also useful when exploiting known structures from the environment, such as the existence of paths to be followed [33,28].…”
Section: Related Workmentioning
confidence: 99%
“…For this purpose we intend to adapt some work on all-terrain obstacle detection [15] [16] to the domain in question. An interesting point of this work is the use of visual attention parallel mechanisms, which we have been shown that, if operating in an intricate way with obstacle avoidance, the amount of processing can be considerably reduced [17], and as a consequence, the computational requirements as well. A key aspect of obstacle avoidance in aquatic environments, yet to be solved, is to filter out false positives induced by waves and large ripples in the water.…”
Section: Progress Beyond the State-of-the-artmentioning
confidence: 99%